2022
DOI: 10.3390/magnetochemistry8050047
|View full text |Cite
|
Sign up to set email alerts
|

Extending NMR Quantum Computation Systems by Employing Compounds with Several Heavy Metals as Qubits

Abstract: Nuclear magnetic resonance (NMR) is a spectroscopic method that can be applied to several areas. Currently, this technique is also being used as an experimental quantum simulator, where nuclear spins are employed as quantum bits or qubits. The present work is devoted to studying heavy metal complexes as possible candidates to act as qubit molecules. Nuclei such 113Cd, 199Hg, 125Te, and 77Se assembled with the most common employed nuclei in NMR-QIP implementations (1H, 13C, 19F, 29Si, and 31P) could potentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…In 2022 Aucar et al 33 developed an LRESC-Loc model to analyze magnetic shieldings with localized molecular orbitals. Kaupp et al 34 reported on evaluation of modern DFT approaches for the computation of nuclear shieldings of 3d transition-metal nuclei and Sauer et al 35 extended NMR quantum computation systems by employing compounds with several heavy metals as qubits. Makulski, Aucar and Aucar 36 studied experimentally and theoretically ammonia in order to establish 14 N and 15 N absolute shielding scales.…”
Section: Progress In Theoretical Methodologymentioning
confidence: 99%
“…In 2022 Aucar et al 33 developed an LRESC-Loc model to analyze magnetic shieldings with localized molecular orbitals. Kaupp et al 34 reported on evaluation of modern DFT approaches for the computation of nuclear shieldings of 3d transition-metal nuclei and Sauer et al 35 extended NMR quantum computation systems by employing compounds with several heavy metals as qubits. Makulski, Aucar and Aucar 36 studied experimentally and theoretically ammonia in order to establish 14 N and 15 N absolute shielding scales.…”
Section: Progress In Theoretical Methodologymentioning
confidence: 99%
“…The usefulness of ZORA calculations of NMR parameters for heavy elements has been shown and reviewed in many studies. [16][17][18][19][20][21][22][23][24][25][26][27][28] Arcisauskaite et al, for example, have previously investigated relativistic effects on Hg chemical shifts in mercury halide compounds. [16] A comparison between three methods were reported: the fully relativistic four-component approach, linear response elimination of small component (LR-ESC), [29,30] and ZORA.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative option are the computationally less demanding two‐component methods [10–15] such as the zeroth‐order regular approximation (ZORA) method. The usefulness of ZORA calculations of NMR parameters for heavy elements has been shown and reviewed in many studies [16–28] . Arcisauskaite et al, for example, have previously investigated relativistic effects on Hg chemical shifts in mercury halide compounds [16] .…”
Section: Introductionmentioning
confidence: 99%